PENERAPAN METODE PEMBELAJARAN CTL UNTUK MENINGKATKAN HASIL BELAJAR PAI DAN BUDI PEKERTI SISWA DI SMPN 2 SUMBERASIH PROBOLINGGO - Faizah Qurotul Ahyun; Muhammad, Devy Habibi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Learning in schools is not only focused on providing material or provision of skills is theoretical knowledge, but also how to make students' learning experiences always associated with actual problems that occur in their environment. That way the author wants to apply a learning method that feels suitable to be applied at SMPN 2 Sumberasih in these problems, namely the author applies the CTL learning method which aims to improve student learning outcomes. Which can collaborate well so that the application of this method can be well received and students can also respond quickly in listening to the material. Not only for students but also can help teachers when KBM takes place, to make it easier to explain and practice it directly in real life. Parents also play an important role in this to support students' interest in learning. This CTL (contextual teaching and learning) learning method is a learning concept that can help teachers learn to link the content to be learned with the real world situation of students and encourage students to make connections between the knowledge they have and its application in their lives as members of the family and community.And with the application of this method it really helps collaboration between teachers and students. As well as students also understand the material better because they can connect the material that has been obtained by the teacher.